Factors Affecting the Performance of Foreign Bank in Malaysia - Ilhomovich, Saidov Elyor (2009)
We analyzed and compared the performance of domestic and foreign banks operating in Malaysia for the period of 5 years, from 2004 to 2008. We found that foreign banks have strong capital, but the statistics show that domestic banks more profitable. However,existing foreign banks are affecting financial services quality in Malaysia, because all banks offer better and low cost banking services for customer during strong competition.In this study used financial ratios of banks by extracting components of CAMEL Model,namely, Capital adequacy, Asset quality, Management, Earnings and Liquidity. To identify the determinants of performance of the Malaysian foreign and domestic banks during 2004-2008 years, this study has chosen multiple regression analysis.The descriptive analysis suggested that the average ROA for the Malaysian commercial banks during the study period was about at 3.21% only. However, it is much better comparing with Asian crisis period, in the beginning of study period; commercial banks shifted their earnings and continued a constant growth thereafter. One more thing is that,in overall local banks show higher ROA than foreign banks. In conclusion, bank performance (including ROA and ROE) of commercial banks in Malaysia influenced by the capital adequacy ratio, total loans to total assets ratio, NPL to total assets ratio,interest expenses to total loans, total operating profit to revenue and loans to deposit ratio.Overall, CAMEL predicts 66.9% of ROA and 64.0% of ROE. We can say that CAMEL is good concept for evaluating bank performance